2022
DOI: 10.1002/oby.23528
|View full text |Cite
|
Sign up to set email alerts
|

T cells dominate peripheral inflammation in a cross‐sectional analysis of obesity‐associated diabetes

Abstract: Objective Myeloid cells dominate metabolic disease‐associated inflammation (metaflammation) in mouse obesity, but the contributions of myeloid cells to the peripheral inflammation that fuels sequelae of human obesity are untested. This study used unbiased approaches to rank contributions of myeloid and T cells to peripheral inflammation in people with obesity across the spectrum of metabolic health. Methods Peripheral blood mononuclear cells (PBMCs) from people with obesity with or without prediabetes or type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…5E and F ), consistent with cytokine outcomes in other inflammatory diseases we have studied. 25-28 These data add to the growing appreciation that steady-state plasma cytokine levels lack the discriminative potential to detect disease-associated changes in circulating immune cell populations that could be actionable.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…5E and F ), consistent with cytokine outcomes in other inflammatory diseases we have studied. 25-28 These data add to the growing appreciation that steady-state plasma cytokine levels lack the discriminative potential to detect disease-associated changes in circulating immune cell populations that could be actionable.…”
Section: Resultsmentioning
confidence: 92%
“… 44 , 45 A growing body of evidence also finds that systemic inflammatory conditions, such as Type 2 diabetes and healthy ageing, have elevated T H 17 responses compared with healthy individuals. 25-28 , 36 From depression to Parkinson’s disease and beyond, the brain has been described to have signatures of T H 17-related inflammation. 20 , 39 , 46 This is also true for AD, where prior reports link T H 17 responses in the brain to AD-related pathology in people and animals.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that nutritional status communicated to T cells via changes in insulin and IGF-1 hormone levels results in a metabolic and functional program that is persistent and maintained. This has clinical relevance, as both insulin and free IGF-1 levels are increased in individuals with obesity, and T cells have been found to dominate peripheral inflammation in obesity in human studies, with Th17 cells having a particularly prominent role 30 32 .…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress and inflammation are key factors in obesity and obesity-related metabolic disorder diseases [ 21 ]. Recently, a report revealed that peripheral T cells secrete TNF-α to contribute to peripheral inflammation and consequently trigger obesity-associated diabetes [ 23 ], indicating that peripheral inflammation dominates the evolution of obesity-related metabolic diseases. Diet and obesity-induced MG production have been documented to be linked to metabolic disease without a deep investigation of the underlying mechanism [ 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%